Clinical and Molecular Characterization of PMP22 point mutations in Taiwanese patients with Inherited Neuropathy. Issue 1 (December 2017) - Liao, Yi-Chu; Tsai, Pei-Chien; Lin, Thy-Sheng; Hsiao, Cheng-Tsung; Chao, Nai-Chen; Lin, Kon-Ping; Lee, Yi-Chung
Abstract Point mutations in the peripheral myelin protein 22 (PMP22 ) gene have been identified to cause demyelinating Charcot-Marie-Tooth disease (CMT) and hereditary neuropathy with liability to pressure palsy (HNPP). To investigate the mutation spectrum ofPMP22 in Han-Chinese population residing in Taiwan, 53 patients with molecularly unassigned demyelinating CMT and 52 patients with HNPP-like neuropathy of unknown genetic causes were screened forPMP22 mutations by Sanger sequencing. Three point mutations were identified in four patients with demyelinating CMT, including c.256 C > T (p.Q86X) in two, and c.310delA (p.I104FfsX7) and c.319 + 1G > A in one each. OnePMP22 missense mutation, c.124 T > C (p.C42R), was identified in a patient with HNPP-like neuropathy. The clinical presentations of these mutations vary from mild HNPP-like syndrome to severe infantile-onset demyelinating CMT.In vitro analyses revealed that bothPMP22 p.Q86X and p.I104FfsX7 mutations result in truncated PMP22 proteins that are almost totally retained within cytosol, whereas the p.C42R mutation partially impairs cell membrane localization of PMP22 protein. In conclusion, PMP22 point mutations account for 7.5% and 1.9% of demyelinating CMT and HNPP patients with unknown genetic causes, respectively. This study delineates the clinical and molecular features ofPMP22 point mutations in Taiwan, and emphasizes their roles in demyelinating CMT or HNPP-like neuropathy.